ANALISIS PARTISIPASI MASYARAKAT DALAM PELATIHAN SISTEM KETAHANAN KEBAKARAN LINGKUNGAN PADA KANTOR PENANGGULANGAN KEBAKARAN DAN PENYELAMATAN SEKTOR JOHAR BARU JAKARTA PUSAT - Sab'an Nasrullah; Bambang Irawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
This study aims to find out the implementation of community participation in the training of environmental fire resistance system in the fire prevention and rescue office of the new johar sector of Central Jakarta. In order for community participation in the training of environmental fire resistance system to run properly requires awareness and awareness of the community to participate in the success of the program.The research method used qualitative descriptive and data collecting technique by interview, observation, literature study and documentation in collecting data which will be the material in this research writing and the researcher took the location at the fire management and rescue office of Johar Baru Sector, Central Jakarta.The result of the research shows that the community's participation has been done well and done, proved by the community members who participated in the training of environmental fire protection system in the area of fire and rescue office of Johar Baru Sector of Central Jakarta. And also the training is carried out in the kelurahan-kelurahan in new Johar district, but in the process of establishment there are still obstacles and obstacles such as lack of communication or socialization to the citizens and the difficulty of community members to participate in SKKL training and the solution is needed a persuasive and conducive approach, focus on improving the capacity of communities who volunteer to participate in SKKL training to participate rather than just achieving certain predetermined goals